Investigating the Performance Skills Of Mathematics Student-Teachers - Salman Al-Sarry, Meeaad Jasim (Opción, 2019)
The current research aims to evaluate the performance skills of the student applied in the fourth stage Mathematics Department morning study, in light of the criteria established in the student evaluation form according to the joint opinion by the academic supervisor and the director and the cooperating teacher in the application school. The aim of the research is to propose strategic steps for the practical education program (the course of observation and application) in the mathematics department for the purpose of develo- ping the practical skills of teaching mathematics. In order to achieve the objectives of the research, the researcher chose the descriptive analytical method, where a questionnaire was prepared by the researcher to evaluate the performance skills of the students applied in the mathematics department. The sample of the study was 60 individuals randomly selected as follows: (20) supervisors in mathematics department, faculty of education / Mustan- siriya University, (20) school principals and (20) cooperative mathematics teachers in middle and middle schools, Where students of the fourth stage / Department of Mathematics / Faculty of Education. In the light of the statistical processes, the study found that the third field (the personal attributes of the applied student) was distinguished by obtai- ning the highest weighted average and the second field (implementation and evaluation) and the first field (planning and preparation in the plan book). Keywords: performance skills.